2021
DOI: 10.1080/17461391.2021.1995509
|View full text |Cite
|
Sign up to set email alerts
|

Ego orientation is related to doping likelihood via sport supplement use and sport supplement beliefs

Abstract: A growing body of evidence suggests sport supplement use is positively related to doping likelihood, both directly and indirectly via beliefs that sport supplements are effective for improving performance. However, it is unclear what leads an athlete to use sport supplements and whether such factors play a role in the supplement-beliefs-doping relationship. To address this issue, we examined whether motivational goal orientations were related to doping likelihood directly and indirectly via sport supplement us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Prior studies showed that athletes who perceived their coach communicating that winning in sports is the most important thing (focused on ego-involving climate) were more likely to indicate a higher doping likelihood [ 31 ] and also doping use [ 8 ]. In contrast, a more task-oriented environment leads to more task-oriented players [ 47 ], and task orientation tends to be negatively related to doping likelihood [ 48 ]. However, in making these comparisons, it should be emphasized that the studies mentioned revealed links between the separate components of an empowering or disempowering climate.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies showed that athletes who perceived their coach communicating that winning in sports is the most important thing (focused on ego-involving climate) were more likely to indicate a higher doping likelihood [ 31 ] and also doping use [ 8 ]. In contrast, a more task-oriented environment leads to more task-oriented players [ 47 ], and task orientation tends to be negatively related to doping likelihood [ 48 ]. However, in making these comparisons, it should be emphasized that the studies mentioned revealed links between the separate components of an empowering or disempowering climate.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the correlates of these two goal orientations has shown they are connected to a wide array of behaviors, cognitions, and beliefs. Regarding behavior, task orientation has been linked to prosocial behavior (Kavussanu, 2006), increased cooperative behavior (Lameiras et al, 2014)-in contrast, high ego orientation has been associated with antisocial behavior (Hurst et al, 2021;Kavussanu, 2006), fear of failure (Go´mez-Lo´pez et al, 2019), and decreased cooperation (Lameiras et al, 2014). In addition, a recent study of cheating in sporting settings found that acceptance of cheating correlated positively with ego orientation and negatively with task orientation, and participants who cheated were more ego-oriented and less task-oriented than others (Ring & Kavussanu, 2018).…”
mentioning
confidence: 99%